THE POTENCY OF LACTUCA SATIVA LINN. AND APIUM GRAVEOLENS L. FROM INDONESIA AS TRANQUILIZER - Sutrisna, Em; Azizah S, Tanti; wuryaningrum, Ariani; Purnama Sari, Mita (International Journal of Ayurveda and Pharma Research, 2015)
Introduction: An attempt to explore the medicinal plants as tranquilizers is relatively rare. Objective: This study aims at examining the sedation effects of 70% ethanolic extract of Lactuca sativa Linn. leaves and antidepressant effects of 70% ethanolic extract of Apium graveolens L. seeds. Material & Method: The animals test used are female mice Swiss strain. The Dose of 70% ethanolic extract of Lactuca sativa Linn. leaves and Apium graveolens L seeds are 200 mg/kg, 400 mg/kg, and 800 mg/kg respectively. The Sedation test uses the rotarod method with diazepam as positive control and anti-depression test uses FST method with amitriptyline as positive control. The sedation test analysis is performed by ANOVA followed by Benferroni test by comparing the fall of time before and after treatment, while the antidepressant analysis test is performed by Kruskal wallis followed by Mann whitney test by comparing the duration of immobility pre and post treatment between groups. Result: In the sedation test, there is significant deference between the 70% ethanolic extract of Lactuca sativa Linn dosage 200; 400 and 800 mg/kg respectively and negative control with p value <0.05 by the Benferroni test. In anti depressant test, the duration of immobility (pre-post treatment) extracts groups shorter than negative control. On Mann whitney test, there are significant difference between the ethanolic extract of Apium graveolens L seeds dose 200; 400 and 800 mg/kg and negative control (p<0.05). Conclusion: The ethanolic extract of Lactuca sativa Linn and Apium graveolens L seeds have potential as tranquilizer.